2024
DOI: 10.1002/jcb.30558
|View full text |Cite
|
Sign up to set email alerts
|

Exploring neuroadaptive cellular pathways in chronic morphine exposure: An in‐vitro analysis of cabergoline and Mdivi‐1 co‐treatment effects on the autophagy–apoptosis axis

Mina Makvand,
Seyed Davood Mirtorabi,
Arezoo Campbell
et al.

Abstract: The complex impacts of prolonged morphine exposure continue to be a significant focus in the expanding area of addiction studies. This research investigates the effectiveness of a combined treatment using Cabergoline and Mdivi‐1 to counteract the neuroadaptive changes caused by in vitro morphine treatment. The impact of Methadone, Cabergoline, and a combination of Cabergoline and Mdivi‐1 on the cellular and molecular responses associated with Morphine‐induced changes was studied in human Neuroblastoma (SK‐N‐MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…SH-SY5Y and SK-N-MC cells have been widely used in neuroblastoma research 16 , 17 and our previous study has shown NVP-BEZ235 (BEZ235), a dual PI3K and mTOR inhibitor 18 declined the expression of PI3K/mTOR pathway-related proteins in both cells. 19 Therefore, both cells were used to evaluate the roles and mechanism of autophagic degradation of the CDK4 on cell cycle distribution.…”
Section: Introductionmentioning
confidence: 99%
“…SH-SY5Y and SK-N-MC cells have been widely used in neuroblastoma research 16 , 17 and our previous study has shown NVP-BEZ235 (BEZ235), a dual PI3K and mTOR inhibitor 18 declined the expression of PI3K/mTOR pathway-related proteins in both cells. 19 Therefore, both cells were used to evaluate the roles and mechanism of autophagic degradation of the CDK4 on cell cycle distribution.…”
Section: Introductionmentioning
confidence: 99%